Learning media transformation: Before, during, and after the COVID-19 pandemic - Fahmi Muhammad Fauzi; Meiyesha Kusdiantie; Muhammad Shidqi’ Abdul Azzam (Hipkin Journal of Educational Research, 2024)
This article discusses the transformation of pre-pandemic, during-pandemic, and post-pandemic learning media, supported by changes in the applicable curriculum. The transition from the Kurikulum 2013 Revisi to the Kurikulum Merdeka is also highlighted. This research aims to understand the development of existing learning media and how the COVID-19 pandemic has influenced it. The study employs a literature review method with a qualitative approach. The findings reveal the development of learning media following the rapid advancement of technology. Before the pandemic, under the Kurikulum 2013 Revisi, traditional media were predominantly used in classrooms with the support of ICT media, which could only be accessed in schools. During the pandemic, digital media significantly grew due to distance learning measures. The emergence of online learning platforms became increasingly popular, with almost all types of learning relying on technology and the internet. In the post-pandemic period, the familiarity with digital media established during the pandemic persisted and was considered easily accessible and highly sought-after. This was further supported by implementing the Kurikulum Merdeka, allowing students to learn anytime and anywhere. Consequently, digital learning media, along with current technology, is currently in high demand.   Abstrak Artikel ini membahas mengenai transformasi media pembelajaran pra atau sebelum pandemi, saat pandemi dan pasca atau setelah pandemi berlangsung. Transformasi media yang didukung pula dengan perubahan kurikulum yang berlaku. Perpindahan dari Kurikulum 2013 Revisi kepada Kurikulum Merdeka. Penelitian ini bertujuan untuk mengetahui perkembangan media pembelajaran yang ada dan bagaimana pandemi COVID-19mempengaruhi hal tersebut. Penelitian ini menggunakan metode literature review dengan jenis penelitian kualitatif. Dihasilkan perkembangan media pembelajaran yang ada mengikuti kemajuan teknologi yang sekarang berkembang dengan pesat. Pada masa sebelum pandemi dengan Kurikulum 2013 Revisi menggunakan media-media tradisional di dalam kelas dengan dukungan media TIK yang hanya dapat di akses di sekolah. Pada masa pandemi, media digital berkembang pesat karena jarak yang berlaku. Munculnya platform belajar online mulai banyak diminati, hampir semua jenis pembelajaran bergantung pada teknologi dan internet. Pada setelah pandemi, dengan terbiasanya menggunakan media digital saat pandemi, setelahnya pun menjadi terbiasa dan dianggap sebagai media yang mudah digunakan dan banyak diminati, didukung dengan penerapan kurikulum Merdeka, di mana peserta didik dapat belajar di mana dan kapan saja, sehingga media pembelajaran digital dengan teknologi saat ini sedang digemari. Kata Kunci: kurikulum 2013; kurikulum merdeka; media pembelajaran; pandemi; pra-pandemi; pasca pandemi